Analisis Pengaruh Pengangguran, Pertumbuhan Ekonomi, dan Pengeluaran Pemerintah terhadap Indeks Pembangunan Manusia di Provinsi Jawa Tengah - Cagar Channani; Marseto Marseto; Sishadiyati Sishadiyati (Jurnal Syntax Admiration, 2024)
The purpose of this study is to identify the relationship and impact of these variables on HDI, as well as provide policy recommendations that can improve the quality of human development in the Central Java Province area. This study uses a quantitative research approach methodology, which is a technique to provide statistical research and programs as answers to data-related research questions. This study examines the influence of poverty, unemployment, and regional income as intervening variables on the Human Development Index in East Java Province in 2010-2019. Multiple linear regression analysis is used to evaluate the data collected using intervening variables. The results show that economic growth and government expenditure are able to increase HDI in East Java Province because many sectors and facilities are prepared by the government to support the quality of life of its people, but unlike the two variables above, unemployment does not have a significant influence on the Human Development Index.